Platypnoea–orthodeoxia syndrome in a patient on haemodialysis: a case report and scoping review - Asomaning, Akosua; Karamchand, Sumanth; Chothia, Mogamat-Yazied (African Journal of Nephrology, 2024)
Introduction: Platypnoea–orthodeoxia syndrome (POS) is a rare condition caused most frequently by an intracardiac right-to-left shunt. Diagnosis requires a high index of suspicion. We report a case of a young man on chronic haemodialysis who developed POS because of superior vena cava obstruction. We also conducted a scoping review of the literature on POS in adult patients. Methods: We followed the PRISMA–ScR guidelines. Studies were eligible for inclusion if they reported on patients with POS in hospitalised adults. We included case reports and case series from 1 January 1949 to 31 May 2023, sought from PubMed (Medline), Web of Science Core Collection, and the Cumulative Index of Nursing and Allied Health Literature. Results: A 29-year-old man undergoing long-term haemodialysis experienced respiratory distress during his dialysis sessions, particularly when seated upright. His oxygen saturation improved to 100% when supine but dropped to 80% when he stood up. Blocking the arteriovenous fistula (AVF) while standing raised his oxygen saturation to 93%. Left heart catheterisation revealed extensive systemic venous collaterals draining into the left atrium via pulmonary veins. A diagnosis of POS from systemic venovenous collateral vessels due to superior vena cava obstruction was made. Because of the patient’s comorbidities and the AVF being his last viable vascular access, no further interventions were pursued. Three hundred and thirty-seven articles (662 patients) were identified in the search of the literature. Six of the patients were on kidney replacement therapy (KRT). The median age was 70 years (IQR 58–79 years). Overall, the most common cause (80%) of POS was an intracardiac right-to-left shunt and patent foramen ovale (PFO) was the most common (74%) primary cause. Hepatopulmonary syndrome (HPS) was the most common extracardiac cause (38%) of POS. Of the six patients on KRT, five had intracardiac causes of POS and one had an extracardiac cause. Most patients (67%) with PFO had percutaneous closure of the shunt. Four of the five patients on KRT with intracardiac shunt had percutaneous or open surgical closure whereas one was managed conservatively. Most of the patients were discharged and had a low mortality rate of only 5%. Conclusions: This case report and literature review describes the causes, treatment, and outcome of POS. Since this is a rare condition, a high index of suspicion is needed for diagnosis. There is a limited number of documented cases in individuals receiving KRT. Although intracardiac shunts were still the most prevalent cause of POS in patients on KRT, SVC obstruction is another aetiology that should be considered. Overall, the prognosis for individuals with POS as reported in the literature was excellent, with a low mortality rate.